Analysis of Digital Information Technology in Improving the Implementation of the Independent Curriculum - Inna Robbani Muthmainnatun; Dian Hidayati (Jurnal Syntax Transformation, 2023)
technology is a innovation and development results from its creators. Digital technology delivers maximum convenience for humans to fulfill various his needs Digital technology is a system Fast counter with processing information form digital codes or values numeric. Before processing , will sensors are required to change information real become digital code. From the results of digital data processing, the information will be displayed on the screen .Implementation of the Independent Curriculum (IKM) is one of the priority programs across main units within the Ministry of Education, Culture , Research and Technology ( Kemendikbudristek ) involving the Curriculum Standards and Educational Assessment Agency (BSKAP ); Directorate General of Early Childhood Education , Basic Education and Secondary Education ( Directorate General of PAUD Dikdasmen ); Directorate General Teachers and Education Personnel ( Directorate General of GTK); as well as Directorate General ( DG ) Vocational .